Evaluation of the intangible cultural heritage in the context of conservation and sustainability of historical settlements in anatolia - Akyildiz, Üyesi Nihal Arda; Olğun, Tuba Nur (Milli Folklor Dergisi, 2020)
Intangible cultural heritage is effective as well as tangible heritage in the conservation of historical and traditional settlements. In settlements and structures where culture is not conserved, only physically conservation practices are made, it is not possible for conservation practices to have sustainable qualifications. Evaluation of tangible and intangible cultural heritage as a whole and implementation of these practices taking into account this evaluation; it is of great importance in terms of transmitting architectural heritage to future generations correctly. In this context, Anatolia emerges as a rich area with its heritage, in which both tangible and. © 2020, Milli Folklor Dergisi. All rights reserved.
Somut olmayan kültürel mirasin anadolu’da tarihî yerleşimlerin korunmasi ve sürdürülebilirliği bağlaminda değerlendirilmesi*
Keywords: Anatolia; Conservation; Historical and traditional settlements; Intangible cultural heritage; Sustainability